A Support for Developers Implement the Accessibility Guidelines Regarding to Web Menus - Antonelli, Humberto Lidio; Fortes, Renata Pontin de Mattos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2015)
Web pages are composed of elements, such as menus that are responsible for assisting navigation on the website. However, many of the menus are not developed properly, which creates accessibility barriers and hinders access to the contents. This paper aims to present a method for creating accessible menus. Initially, we studied the different types of menus and the accessibility guidelines involving the creation of accessible menus. From the studies, we developed a meta-model that gave rise to AMenu language, where we included all the technical details regarding to accessibility. Then, we developed the AMeG tool to facilitate the use of language. Finally, we conducted a case study with developers, in order to verify the feasibility of the approach, arguing its efficiency and limitations. The results indicate a reduction in efforts to develop accessible web menus, since developers do not have to deal with technical details of accessibility